1978
DOI: 10.1128/iai.19.3.950-960.1978
|View full text |Cite
|
Sign up to set email alerts
|

Reversion of dextran sulfate-induced loss of antibacterial resistance by Bordetella pertussis

Abstract: Parenteral injection of dextran sulfate 500 (DS 500; 50 mg/kg of body weight) into mice caused a complete loss of resistance to a sublethal (2 x 103 to 5 x 103) infection with Listeria monocytogenes. Such loss could be prevented by pretreatment of animals with 3 x 109 heat-killed Bordetella pertussis organisms (PO) 5 to 30 days before the administration of DS 500. The increased phagocytic capacity induced by PO was only exhausted when a fourfold dose of DS 500, effecting complete loss of antibacterial resistan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
12
0

Year Published

1978
1978
1988
1988

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 17 publications
3
12
0
Order By: Relevance
“…In contrast, the decrease in resistance observed after simultaneous infection and with killed B. pertussis organisms was much more pronounced in LPS-sensitive strains. Analogous with these findings are previous studies which demonstrated that LPS can only partially substitute for killed B. pertussis organisms in overcoming dextran sulfate-induced loss of resistance to infection (10).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…In contrast, the decrease in resistance observed after simultaneous infection and with killed B. pertussis organisms was much more pronounced in LPS-sensitive strains. Analogous with these findings are previous studies which demonstrated that LPS can only partially substitute for killed B. pertussis organisms in overcoming dextran sulfate-induced loss of resistance to infection (10).…”
Section: Discussionsupporting
confidence: 80%
“…Infection with Listeria monocytogenes. Infection with L. monocytogenes, a facultative intracellular parasite, was performed by the method of Mackaness (14), employing L. monocytogenes serotype 4b as published elsewhere (10). At certain intervals after the intravenous infection, the germ numbers in the spleen were evaluated by culture of homogenized splenic tissue in a 10-fold dilution in tryptose agar (Difco Laboratories, Detroit, Mich.).…”
Section: Methodsmentioning
confidence: 99%
“…Histological evaluation. Mice infected with L. monocytogenes serotype 4b developed an intense inflammation corresponding to that previously described by others (9,11,13) and by our group (4,6). Three days after infection, numerous pyogenic foci with or without necrosis were present in the livers of experimental animals (Fig.…”
Section: Resultssupporting
confidence: 81%
“…Thus, it is of interest to deternine the effects on virus infection of other agents that inhibit macrophage function without causing significant macrophage toxicity. Trypan blue and dextran sulfate have both been demonstrated to inhibit macrophage lysosomal function and to inhibit host responses that require macrophage participation (5,(7)(8)(9). In the present studies we have compared the effects of dextran sulfate and trypan blue with those of silica on systemic intravenous (i.v.)…”
mentioning
confidence: 99%
“…with 0.9% NaCl 2 h before viral infection. The regimens used for the macrophageinhibitory agents were those that have been documented to be effective in decreasing macrophage function in various microbial and tumor systems (5,7,9,13,15,21). To establish that macrophages were affected, peritoneal exudate cells were obtained after treatment of mice and characterized according to morphological examination, using the Wright staining procedure, phagocytosis of latex and presence of nonspecific esterase (29), which provide a more precise iden-624 NOTES tification of macrophages than does morphology alone.…”
mentioning
confidence: 99%